Camille Gutt : les finances et la guerre 1940-1945 - Crombois, Jean-François; Godeaux, Jean; Vanden Abeele, Michel (Gerpinnes Bruxelles : Quorum CEGES, 1999)
Bibliotheek François Vercammen
Frans
Monografie